Descrição da rede de saúde de São Carlos, SP, por meio de um estudo de caso sobre a experiência de uma pessoa afetada pelo câncer - Villari, Ana Paula Silva (2013)
This study had the objective to discourse about the integrality of Sao Carlos-SP county care network, from the experience of a person with cancer, by means of a case study. From the narrative of subject's focal it has been done the triangulation of respective findings interviewing other two people identified as strategic for reaching mentioned objective, therefore appointed as units of analysis of subject s focal. It has been detected that local Health Care System of São Carlos-SP is under a transition process seeking for a model that proposes expanded and integral care for everyone without distinction. This system currently is overloaded and slow, facing attendance quality problems and discomfort of management responsible, care employees personal and health care system user. In order to overcome these problems, it will be necessary investment on Family Strategic Health program, practice of attendance humanization and health care professional qualification. It will also be necessary to increase the installed capacity, qualify the regulation strategic, improve the communication between management and attendance professionals, organize a care network oriented by care lines and agree on Health System building process with users and professional team.